Racism Against Korean-American Adoptee in Blue Bayou Movie (2021) - Kamardikan, Fitta Rizqi Catur; Hidayah, Atinia (Metaphor, 2025)
The purpose of this study is to examine Blue Bayou (2021), an American drama film written and directed by Justin Chon. The issues that need to be addressed are (1) how racism against Korean-American adoptees is portrayed in the movie, and (2) how society's response to racial differences is shown in Blue Bayou (2021). The purpose of this research study is to assess the film Blue Bayou (2021) through the use of a descriptive qualitative method. The study method's data collection steps include reading and watching, recognizing, categorizing, and choosing. using data collecting, data reduction, data display, and conclusion to analyze the research method's data. Data analysis techniques used by the researcher include exhibiting, explaining, and interpreting. The study's findings were as follows: (1) Racism can take many different forms, such as individual, systemic, and colorism. (2) The way that society responds to people of different races includes pity, empathy, ignorance, and punishing those who practice racism.